Peripheral microangiopathy in Eisenmenger syndrome: A nailfold video capillaroscopy study. (1st August 2021) - Arvanitaki, Alexandra; Giannakoulas, George; Triantafyllidou, Eva; Feloukidis, Christos; Boutou, Afroditi; Garyfallos, Alexandros; Karvounis, Haralambos; Diller, Gerhard-Paul; Gatzoulis, Michael A.; Dimitroulas, Theodoros
Abstract: Background: Eisenmenger syndrome (ES) comprises a severe phenotype of pulmonary arterial hypertension characterized by angiopathy of the lung circulation. The aim of the present study was to demonstrate the presence of systemic microvascular abnormalities in patients with ES using nailfold video-capillaroscopy (NVC) and to identify potential correlations of nailfold capillaroscopic characteristics with non-invasive markers of systemic organ function. Methods: Α cross-sectional NVC study was performed in 17 consecutive patients with ES and 17 healthy controls matched for age and sex. NVC quantitative (capillary density, capillary dimensions, haemorrhages, thrombi, shape abnormalities) and qualitative (normal, non-specific or scleroderma pattern) parameters were evaluated. Results: Patients with ES [median age 40 (18–65) years, 11 women] presented reduced capillary density [8.8 (7.2–10.2) loops/mm vs. 9.9 (8.3–10.9) loops/mm, p = .004] and increased loop width [15.9 (10.3–21.7) μm vs. 12.3 (7.6–15.2) μm, p < .001], while they had significantly more abnormal capillaries than healthy controls [2.5 (0.9–5.4) abnormal loops/mm vs. 1.0 (0.0–1.7) abnormal loops/mm, p < .001]. NVC shape abnormalities in ES were positively correlated with NT-proBNP (r = 0.52, p = .03) and were negatively associated with estimated glomerular filtration rate (r = −0.60, p = .02). Additionally, capillary loop diameter was positively correlated with increased haemoglobin levels (r = 0.55, p = .03) and negatively correlated with reduced peripheral oxygen saturation (r = − 0.56, p = .02). Conclusions: This study supports the hypothesis of peripheral microvascular involvement in ES parallel to pulmonary microangiopathy detected by NVC. Further longitudinal studies are needed to confirm our preliminary results. Graphical abstract: Unlabelled Image Highlights: Microangiopathy in Eisenmenger syndrome is not strictly restricted in the pulmonary vascular bed. Peripheral microvascular alterations are demonstrated with nailfold video-capillaroscopy. Capillaroscopic abnormalities correlate with markers of cardiac and renal dysfunction and indices of chronic hypoxia.